Towards consensus in acquisition and image analysis of PET and SPECT in the assessment of cardiac sympathetic innervation: a mini-review - Walter Noordzij; Andor W. J. M. Glaudemans; Luis E. Juarez‑Orozco; Riemer H. J. A. Slart (SPRINGER-VERLAG ITALIA SRL, 2022)
In the rapidly evolving field of nuclear medicine, imaging cardiac sympathetic innervation using both conventional nuclear medicine and PET tracers is a small but growing field of interest. Recent larger clinical trials have underlined the importance of imaging cardiac sympathetic innervation as well as the consequences of low regional tracer accumulation for patient outcomes. New developments have resulted in the introduction of novel PET tracers with high clinical potential, especially for imaging centers without an on-site cyclotron. Despite the generated guidelines, especially on MIBG scintigraphy, widespread compliance with standardization efforts for cardiac sympathetic innervation imaging has not been yet achieved. Compliance with standardization of imaging acquisition and data analysis is crucial to move forward towards refinement of clinical guidelines.